Amentoflavone Ameliorates Carrageenan-Induced Pleurisy and Lung Injury by Inhibiting the NF-κB/STAT3 Pathways via Nrf2 Activation - Hou, Tianhua; Yang, Manshi; Yan, Kun; Fan, Xiaoye; Ci, Xinxin; Peng, Liping (Frontiers in Pharmacology, 2022)
Many natural flavonoids can activate nuclear factor erythroid 2-related factor 2 (Nrf2), which is pivotal for alleviating various diseases related to inflammation and oxidative stress, including pleurisy. Amentoflavone (AMF), a biflavonoid extracted from many plants, has some beneficial bioactivities, especially anti-inflammatory and antioxidative activities. We aimed to investigate whether AMF protects against pleurisy and lung injury induced by carrageenan (Car) by activating Nrf2.Pleurisy was induced in wild-type (WT) and Nrf2-deficient (Nrf2-/-) mice. Then, pleural exudate and lung tissue were collected for biochemical analysis, H&E staining, immunocytochemistry and western blotting.Our results indicated that AMF protected against Car-induced pleurisy and lung injury. The Wright-Giemsa and H&E staining results showed that AMF alleviated inflammatory effusion and pathological injury. In addition, AMF decreased SOD and GSH depletion and MDA and MPO generation in the lung tissue of mice. AMF activated Nrf2 through keap-1 dissociation and subsequently increased heme oxygenase-1 (HO-1), NAD(P)H-quinone oxidoreductase 1 (NQO1), γ-glutamylcysteine ligase (GCL) levels. Furthermore, AMF suppressed IL-1β and TNF-α and increased IL-10 in the pleural exudate by blocking the proinflammatory NF-κB, signal transducer and activator of transcription 3 (STAT3) and extracellular signal-regulated kinase (ERK) pathways induced by Car. However, these antioxidative and anti-inflammatory effects were weakened in Nrf2-/- mice. Moreover, AMF failed to suppress the NF-κB and STAT3 pathways in Nrf2-/- mice.Our results demonstrated that AMF exerted anti-inflammatory and antioxidative effects on lung injury and pleurisy induced by Car in a Nrf2-dependent manner.